Women “cumbiando” the world: the feminist proposal of Corroncha Son - Núñez Moya, Jáirol (2022)
The article analyzes the proposal of the musical group Corroncha Son, which emerged in Mexico in 2018. For this, its music is considered, based on genres such as Colombian cumbia, son jarocho and rap; and criticism, associated with the fight for women's rights. For the analysis, the approaches of gender studies and the relevance of feminisms are considered as a necessary position in contemporary society. Music and representation are a critical medium used by the musical group in order to position itself in relation to patriarchal society, developing a counter-hegemonic proposal, which is shown to us in its staging, in its lyrics and in the claim that performed.